Analysis of the Mathematical Reasoning Ability of High School Students in Solving Trigonometric Problems - Hildegardis Kono Oemanas Oemanas; Selestina Nahak; Ferdinandus Mone; Camilo Andrés Rodríguez-Nieto (Indonesian Educational Research Journal, 2024)
Reasoning is needed by students to solve trigonometry problems that are considered difficult to solve. So, the researcher conducted a study to determine students' mathematical reasoning skills in solving trigonometric problems. This type of research is descriptive research with qualitative methods. The subjects of this study were 3 students of class XII in one of the senior high schools in North Central Timor district. Data collection techniques were test questions and interviews. From the results of the study, it was concluded that high category mathematical reasoning ability was able to fulfill 4 reasoning indicators, medium category mathematical reasoning ability was able to fulfill 2 reasoning indicators, while low category reasoning ability only fulfilled 1 reasoning ability indicator.